(untitled) (Indian Journal of Animal Production and Management, 2024)
This study evaluated the impact of dietary supplementation with peppermint and lemongrass essential oils (EOs) on various biochemical parameters in lactating dairy cattle over 90 days. The experiment was conducted at the Instructional Dairy Farm, GBPUA&T, Pantnagar, Uttarakhand, India, and involved 18 animals divided into three groups. The control group (T0) animals received a basal diet, while in T1 group animals, concentrate was supplemented with 0.1% peppermint EO and T2 groups with 0.1% lemongrass EO. Blood samples were collected on day 0, and after 30, 60, and 90 days for the study of hematological and antioxidant parameters. Hematological parameters viz. Hb, TEC, PCV, eosinophil, monocyte, platelets, MCV, MCH, and MCHC, remained within normal ranges across all groups, with no significant differences observed. However, TLC and neutrophil concentrations were significantly (P<0.05) lower, and lymphocytes were significantly (P<0.05) higher in the lemongrass EO group (T2) compared to the control group (T0). Antioxidant analysis revealed that SOD levels were significantly (P ≤ 0.01) higher in lemongrass EO group (T2), while LPO levels were significantly (P ≤ 0.01) lower in T2 compared to T0. Overall, the results suggested that lemongrass oil supplementation improves immunity and antioxidant status in dairy cattle without significantly affecting hematological parameters.